CULTURAL MATERIALISM IN CORMAC MC CHARTY'S NO COUNTRY FOR OLD MEN MATERIALISME KULTURAL DALAM NOVEL NO COUNTRY FOR OLD MEN KARYA CORMAC MC CHARTY - Omega Mega Robinsyah Yudhistira; Meilia Adiana; Hat Pujiati (Publika Budaya, 2014)
No Country For Old Men is written by Cormac Mc Charty which is set in the boarderline of Mexico and Texas. The story centers on Chigurh who is a professional paid killer during the glorious time of the drug dealers and mafia. The environment has highly influenced his personality about vice and virtue. In the story the strongest order comes from the capital drug dealers which make them rule the way of life. In contrast, the police as the agent of virtue can not be a great benefactor to the citizen, since in the story the sheriff is never be able to catch or even meet Chigurh in person during his act as a peculiar serial killer. To study this phenomenon, the inductive method is employed to understand the position of power which leads to strongest doctrine that has major influence to influence Chigurh’s behavior as a psychopath. Killing people becomes habit for such man who sees and kills people in daily activity. Furthermore, the environment forces him to do so. Gun becomes friend, and money is the purpose. By this peculiar environment, Chigurh has grown into a psychopathic killer with his own motive that was different by the other people. Money is no longer his sole purposes but pleasure and determined principle. This chaotic environment has established a new ideology which continues to the process of cultural materialism. Raymond William as the successor of Marxist teaching has proven that there is a way for people to adjust with his environment no matter how far it is peculiar since there is a class structure in the society. The final chapter of the novel ends with the survival of the evil and inability of the virtue. The story teaches that the strongest doctrine of the time could triumph over someone’s nature. Keywords: class structure, cultural materialism, ideology, marxist teaching, psychopath, relation of power, vice and virtue,